Reduction of NEP variations for terahertz detectors using Schottky barrier diodes in CMOS. Issue 11 (5th May 2017) - Kim, D.Y.; O, Kenneth K.
Abstract : Variations of low‐frequency noise including flicker and Lorentzian spectra are the dominant source of variation of noise equivalent power (NEP) for terahertz detectors using diode‐connected N‐type MOS (NMOS) transistors. The low‐frequency noise of Schottky diodes fabricated in the same CMOS process as the NMOS detectors are dominated by generation and recombination noise. At 1 MHz modulation frequency, the noise of Schottky barrier diodes (SBDs) and its variation are ∼2× lower than those of diode‐connected NMOS transistors. It should be possible to reduce the variation of NEP by ∼2× using Schottky diode detectors modulated at 1 MHz.